Ethics in Freud’s Theory and Its Comparison With Ethics From the Perspective of Islam - Amir Qorbanpour Lafamajan; hamid qorbanpoorlafmejani,; abdolhossain khosropanah, (Health, Spirituality and Medical Ethics, 2022)
Background and Objectives: Psychology needs to study ethics as an important dimension of human personality. The present study aims to critique the moral foundations of Freud's theory based on Islamic ethics. Methods: This is a review study. We used library and internet studies, and the resources related to the subject were extracted and studied. Results: According to Freud, ethics results from internalizing parental and social values and relative, masculine, illogical, and irrational matters. A human being is morally neutral. The criterion for moral behavior is to follow the moral standards of parents or the community. On the contrary, according to Islam, man is not morally neutral but has a spiritual morality. Part of morality is introduced by nature and intellect, and the other is introduced by religious teachings. Islamic morality is absolute and is not subject to the tastes of individuals or social conventions, and its audience is a kind of human being. Proximity to God is the criterion for evaluating moral behaviors, and to achieve this goal, both the appearance of the behavior and the motivation of the doer must be good and divine. Conclusion: The most important critique of Freud’s moral view from the perspective of Islamic morality is to ignore the innate moral capacities of man, consider moral matters as irrational, relativize moral propositions, limit morality to masculinity, and pay attention to the appearance of moral behaviors and ignore the role of intention in the formation of moral behaviors.